Domestic pet dogs (Canis lupus familiaris) do not show a preference to contrafreeload, but are willing - Liza Rothkoff; Lynna Feng; Sarah-Elizabeth Byosiere (Scientific Reports, 2024)
Abstract Contrafreeloading is the behavior of working for food when also provided with identical food that does not require effort to obtain. This behavior has been observed in humans and non-human animals, including domesticated species. In the current investigation, we assessed whether companion animals, specifically domestic dogs, contrafreeload when presented with two feeders simultaneously, a snuffle mat (a work for food device) and a tray (a freely available food device). Thirty-eight pet dogs participated in the study in which ten feeding trials were presented where food was distributed equally in both feeders. Three overarching research questions were considered: (1) Do dogs prefer to contrafreeload and/or are they willing to contrafreeload, (2) is activity (step count) or body condition score (BCS) related to contrafreeloading behavior and, (3) does previous experience with puzzle feeders impact contrafreeloading behavior? Two general linear models were conducted assessing the effects of sex, experience, age, activity and BCS on the proportion of first choices to the snuffle mat (IC s ) and the number of interactions with the snuffle mat while food was still available in the tray (IN s ) . Overall, when assessing the proportion of first choices to each feeder, dogs demonstrated a willingness to contrafreeload but not a preference to contrafreeload. In a reduced model, only one term, owner-reported body condition score, had a significant effect, suggesting that dogs with a higher BCS demonstrated a greater proportion of first choices for the snuffle mat (F (1,36) = 7.72, p = 0.009, η2p = 0.177). In evaluating the number of interactions with the snuffle mat while food was still available in the tray, the model was not significant (F (5,29) = 1.231, p = 0.320, η2p = 0.175). This study represents the first investigation of contrafreeloading in domestic pet dogs and informs recommendations for canine enrichment.